2009
DOI: 10.1016/j.jcrs.2009.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment imaging in the management of postoperative fibrin pupillary–block glaucoma

Abstract: Postoperative fibrin pupillary-block glaucoma, an uncommon complication of intraocular surgery, develops when an inflammatory fibrin membrane occludes the pupil, resulting in peripheral angle closure. We present a series of 4 patients with this condition and describe the role of anterior segment optical coherence tomography and ultrasound biomicroscopy in distinguishing fibrin pupillary-block glaucoma from other forms of postoperative acute glaucoma. Specific to this condition is the presence of a fibrin membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 9 publications
0
28
0
2
Order By: Relevance
“…After cataract surgery, an increased IOP and a narrowed anterior chamber can develop due to fibrin membrane-dependent pupillary block, Soemmering's ring, posterior synechia, capsular block syndrome, and malignant glaucoma (1,2). Although fibrin membrane-dependent PBG is frequently seen after pars plana vitrectomy (PPV), there are a few studies on its development after cataract surgery (3).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After cataract surgery, an increased IOP and a narrowed anterior chamber can develop due to fibrin membrane-dependent pupillary block, Soemmering's ring, posterior synechia, capsular block syndrome, and malignant glaucoma (1,2). Although fibrin membrane-dependent PBG is frequently seen after pars plana vitrectomy (PPV), there are a few studies on its development after cataract surgery (3).…”
Section: Discussionmentioning
confidence: 99%
“…In this particular situation, the aqueous accumulates in the posterior chamber as the fibrin membrane completely covers the pupilla. It was reported that 3 of these 4 patients had diabetes mellitus (DM) (2). On the other hand, previous reports suggest that the development of fibrin reaction after cataract surgery in patients with DM is associated with an impaired blood-aqueous barrier (5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations